2009
DOI: 10.1002/cbm.737
|View full text |Cite
|
Sign up to set email alerts
|

Predicting juvenile delinquency: The nexus of childhood maltreatment, depression and bipolar disorder

Abstract: Background It is important to identify and provide preventative interventions for youth who are most at risk for offending behaviour, but the connection between early childhood or adolescent experiences and later delinquency adjudication is complicated.Aim To test for associations between specified mental disorders or maltreatment and later delinquency adjudication.Method Participants were a random sample of youth before the juvenile courts in two Northeast Ohio counties in the USA (n = 555) over a 4‐year time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…Researches found that the adolescent influenced by depression and anxiety achieved lower level of social skill, self-esteem, and academic performance [4] [5]. They were also easier to have problematic behaviors, criminal behaviors [6] [7], and mental health problems [8]. These may be related to the idea that how to value children's behavior in Chinese society.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Researches found that the adolescent influenced by depression and anxiety achieved lower level of social skill, self-esteem, and academic performance [4] [5]. They were also easier to have problematic behaviors, criminal behaviors [6] [7], and mental health problems [8]. These may be related to the idea that how to value children's behavior in Chinese society.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Mental health difficulties are linked to later youth offending behavior and delinquency adjudication, though it is not clear if this link is direct or if these difficulties lead to other risk factors or poor decision-making (Grisso, 2008;Heilbrum, Goldstein, and Redding, 2005;Mallett, Stoddard-Dare, and Seck, 2009). Early childhood aggressive behaviors have been found predictive of later delinquent activities (Kashani, Jones, Bumby, and Thomas, 1999;Tremblay and LeMarquand, 2001).…”
Section: Mental Health and Substance Abuse Problemsmentioning
confidence: 99%
“…Research has also found that a substantial proportion of individuals in the juvenile delinquency population meet diagnostic criteria for a psychiatric disorder, with estimates ranging from 40-70% (Fazel et al, 2008;Mallett, Dare, & Seck, 2009;Skowyra & Cocozza, 2006). Several mental health conditions have been linked empirically to juvenile delinquency (Courneau & Lanctôt, 2004;Loeber & Keenan, 1994).…”
Section: Special Education Diagnosismentioning
confidence: 99%
“…For example, hyperactivity and attention deficits have been linked to risk-taking behaviors and violent offending (Hawkins et al, 1998). Childhood depression has been linked to stealing and physical aggression (Loeber & Keenan, 1994;Mallett et al, 2009). The most common psychiatric disorders found among the juvenile delinquency population include externalizing disorders such as Attention Deficit/Hyperactivity Disorder, Conduct Disorder, and Oppositional Defiant Disorder, as well as substance use, anxiety, and mood disorders (Skowyra & Cocozza, 2006).…”
Section: Special Education Diagnosismentioning
confidence: 99%